PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI MAN 3 KABUPATEN BIREUEN - Zakiah Zakiah; Endang Syahriani; Sri Yanna (LPPM-UNIKI, 2023)
This study aims to analyze the relationship between work environment, teacher motivation and job satisfaction which contribute to teacher performance. The research was conducted on teachers of State Madrasah Aliyah (MAN) 3 Bireuen. Using path analysis. Data was collected through valid and reliable questionnaires. The research results show; 1) between exogenous variables namely work environment, work motivation and teacher job satisfaction have a positive correlation with an average between 0.46 to 0.56. 2) there is a direct and indirect influence of the work environment on teacher performance of 42.14%, between work motivation on teacher performance of 45.55% and job satisfaction on teacher performance of 47.74%. 3) Simultaneously work motivation, work motivation and job satisfaction make a positive contribution of 71,1% to the performance of MAN 3 Bireuen teachers.